Interferon Regulatory Factors Functioned as Activators of the Interferon Pathway in the Scallop Chlamys farreri - Hu, Naina; Lian, Shanshan; Zhu, Xiaomei; Chen, Xiaomei; Sun, Fengzhi; Zhang, Lingling; Wang, Shi; Bao, Zhenmin; Hu, Jingjie (Frontiers in Marine Science, 2022)
Interferon regulatory factors (IRFs) are a family of transcription factors that control many facets during innate and adaptive immune responses. Vertebrate IRFs play important roles in regulating the expression of interferons (IFNs) and IFN-stimulated genes, while only limited studies were conducted on invertebrate IRFs. In the present study, four IRF family genes (CfIRF1, CfIRF1-like, CfIRF2, and CfIRF8) were identified from Zhikong scallop (Chlamys farreri) through whole-genome scanning. CfIRFs contain a highly conserved N-terminal DNA-binding domain and a variable C-terminal regulatory domain. CfIRFs were constitutively expressed during development as well as in adult tissues, especially in hepatopancreas, hemolymph, gill, and mantle. In hemolymph, qRT-PCR analysis revealed that CfIRF1, CfIRF1-like, and CfIRF2 were significantly upregulated in response to Vibrio anguillarum infection, and their encoding proteins could translocate into nucleus. Dual-luciferase reporter assay on CfIRF1, CfIRF1-like, and CfIRF2 showed that these three proteins were capable to induce a strong activation of ISRE promoters. Notably, in comparison with CfIRF1 and CfIRF1-like, CfIRF2 showed the most sensitive responses in coping with V. anguillarum, and consistently, CfIRF2 exhibited the most significant activation on ISRE. This study would provide valuable information for the innate immune roles of the IRF gene family in bivalve molluscs.